2019
DOI: 10.1097/bor.0000000000000663
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary involvement in antisynthetase syndrome

Abstract: Purpose of review Lung involvement is a distinctive feature of antisynthetase syndrome (ASS) and it is considered a basic disease-classifying criterion. In this review, we go over clinical features, radiological patterns, prognostic factors, pathogenesis and treatment of lung involvement in ASS patients, focusing on the clinical differences linked to the different antibody specificities known so far. Recent findings The lung is the most common extramusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 80 publications
3
39
1
4
Order By: Relevance
“…NSIP has been reported as the most common pattern on HRCT in patients with ILD secondary to autoimmune etiology, in particular in patients with antisynthetase syndrome, followed by OP. Less common is the occurrence of usual interstitial pneumonia [8][9][10]. In our case series, only half of the patients presented with cellular NSIP and OP patterns.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…NSIP has been reported as the most common pattern on HRCT in patients with ILD secondary to autoimmune etiology, in particular in patients with antisynthetase syndrome, followed by OP. Less common is the occurrence of usual interstitial pneumonia [8][9][10]. In our case series, only half of the patients presented with cellular NSIP and OP patterns.…”
Section: Discussionmentioning
confidence: 53%
“…Less commonly, usual interstitial pneumonia (UIP) and acute interstitial pneumonia (AIP) have been reported. Nevertheless, the evidence is currently based on retrospective studies or case reports [8][9][10]. In our clinical practice, we often encountered patients finally diagnosed with ASS who had HRCT findings reported to be less frequent in this syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanic's hand is major sign of rheumatic diseases. Previous research suggested that pulmonary arterial hypertension has a low prevalence in ASS-IP compared with other CTDs, but it independently affects prognosis and survival [21].…”
Section: Discussionmentioning
confidence: 96%
“…RPILD typically occurs in association with anti-MDA5 antibodies, whereas ILD with insidious onset, a pattern of non-specific interstitial pneumonia (NSIP) and adequate response to immunosuppression is found in the context of anti-aminoacyl-tRNA-synthetase antibodies, most frequently anti-Jo-1 (histidyl-tRNA synthetase) (Sato et al, 2009;Koreeda et al, 2010;Chen et al, 2013;Gasparotto et al, 2019). Intriguingly, the epitopes targeted by these autoantibodies reside in two unrelated cytoplasmic proteins: MDA5 represents a helicase that binds double-stranded RNA and functions as an antiviral pattern recognition receptor (Reikine et al, 2014), whereas histidyl-tRNA-synthetase generates histidyl-tRNA, which incorporates histidine into polypeptide chains (Freist et al, 1999).…”
Section: Introductionmentioning
confidence: 99%